Still 'Regime Competition'?: Trade Unions and Multinational Restructuring in Europe - Pulignano, Valeria (Relations industrielles / Industrial Relations, 2006)
This article studies trade unions' response to transnational change in a large multinational corporation within the motor industry in Europe. We show how the use of the European Works Councils (EWCs) as a forum for European negotiation did not counter the management's effort to whipsaw trade unions, such as to play off workers against each other in local negotiations. This seems to suggest that the effort to network and coordinate between employee representatives, and to negotiate with management through 'active' EWCs is ineffective at controlling inter-union competition in cases of transnational restructuring. Hence, research outcomes illustrate that an analysis of the impact of European-level agreements on plant level is requested in order to assess the effectiveness of 'active' EWCs in forging cross-national links.
Keywords: Agreements; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Motor vehicle industry; Multinational corporations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Trade Unions in Europe: Meeting the Challenge - Pulignano, Valeria (Relations industrielles / Industrial Relations, 2004)
The book, "Trade Unions in Europe: Meeting the Challenge," edited by Deoborah Foster and Peter Scott, is reviewed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Business conditions; Economic conditions; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Globalization, Restructuring and Unions: Transnational Co-ordination and Varieties of Labour Engagement - Pulignano, Valeria; Lucio, Miguel Martínez; Walker, Steve (Relations industrielles / Industrial Relations, 2013)
The structure, content and space of union transnational co-ordination are much richer and complex than simply revolving around tensions and relations between bureaucrats and local activists. This is illustrated through the ETUC TRACE project, a study of a managed and steered form of international union coordination. Drawing on this study, this paper discerns a form of co-ordination that worked across various dimensions of action (i.e. "influencing" politics and "communicating" policy), various political relations (internal and external relations) and different organizational levels (micro and macro). By adding original material to the existing literature, the paper stresses the relevance of the project and the various dimensions for appreciating the problems unions face in establishing and sustaining effective cross-national coordination and a supportive environment of "union learning". The TRACE project acknowledged the need to build coordination through a variety of means and serves as an invaluable insight and lesson into more managed and conscious forms of coordination.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Coordination; Globalization; Labor Unions; Management theory; Organizational learning; Project management; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies